THE AUTHORâ€™S ARRANGEMENT OF EVENTS IN MOYESâ€™S ME BEFORE YOU - Gusti Ayu Made Rai Suarniti (Universitas Warmadewa, 2018)
This writing focused on â€œThe Authorâ€™s Arrangements of Events in Moyesâ€™s Me Before You (2012).â€ This writing is aimed to analyze the causal relationships of those events in Me Before You. The theory applied for analyzing the problem is the theory of arrangement of event, well known as plot taken from William Kenney. The method which is used in this research consist of three steps. Those are data source, data collection, data analysis, and presenting data. The data source is taken from Moyesâ€™s Me Before You. The data are collected by using observation method then it is analyzed descriptively based on the theoretical concept and presented by using informal method. Based on the result of the data analysis, it can be stated that the authorâ€™ s arrangement of events ( plot) in Me Before You consists of three parts, those are: beginning structure, middle structure, and the end structure. The beginning structure consist of exposition of the character and setting. The middle structure consist of social conflict, complication and climax. Finally, the end structure of this novel, the author tells us about the main character (William Traynor) decided to die of suicide way.